The impact of the flipped classroom on the motivation and academic performance of Chinese college English learners - Zhonger Wang; Jin Lu; Shenchen Yu (PLoS ONE, 2025)
The flipped classroom exemplifies the concept of active teaching; nevertheless, its effects on learning motivation and academic performance remain somewhat inconsistent. In this research, a sample of 70 sophomore students from China was selected and divided into an experimental group (comprising 35 students) and a control group (also 35 students). A four-month quasi-experiment was then conducted, with the experimental group implementing the flipped classroom teaching approach, while the control group adhered to the traditional teaching method. Before and after the experiment, a questionnaire covering four factors, which was determined through exploratory and confirmatory factor analyses of 611 college students, was used to measure the changes in students’ English learning motivation, and two English proficiency tests of the same difficulty level were also conducted. The research results of the independent t test between the two groups showed that the overall motivation level of the experimental group was significantly improved. Specifically, in terms of integrative motivation, the mean value of the post-test in the experimental class was 3.53, with a standard deviation (SD) of 0.90, a t-value of 2.651, a P-value of 0.010* and a Cohen’s d of 0.634; in terms of instrumental motivation, the mean value of the post-test was 3.34, with a SD of 0.91, a t-value of 2.881, a P-value of 0.005** and a Cohen’s d of 0.689; in terms of autonomous learning motivation, the mean value of the post-test was 3.84, with a SD of 0.78, a t-value of 5.569, a P-value of 0.000**and a Cohen’s d of 1.331; in terms of intrinsic motivation, the mean value of the post-test was 3.58, with a SD of 0.94, a t-value of2.889, a P-value of 0.005**and a Cohen’s d of 0.691; from the perspective of total motivation, the mean value of the post-test was 3.58, with a SD of 0.69, a t-value of 4.477, a P-value of 0.000**and a Cohen’s d of 1.070. Meanwhile, the total score of the English test in the experimental group was also significantly increased in the independent t test. The mean value of the post-test in the experimental class was 68.06, with a SD of 8.00, a t-value of 3.336, and a P-value of 0.001**and a Cohen’s d of 0.797. Through correlation analysis, it was found that the above four factors had a significant positive correlation with English scores. Further multivariate linear regression analysis was carried out, taking the four motivation factors as independent variables and English scores as dependent variables. The results showed that autonomous learning motivation (P = 0.022* < 0.05) and intrinsic motivation (P = 0.001** < 0.01) made significant contributions to predicting English scores, and the variance inflation factor (VIF) value was less than 5, indicating that there was no multicollinearity problem. In conclusion, this study confirms that the flipped classroom can effectively stimulate students’ English learning motivation and improve their scores. Accordingly, it is recommended to focus on cultivating students’ autonomous learning motivation and intrinsic learning motivation in the teaching process.